The Immersive Mental Rotations Test: Evaluating Spatial Ability in Virtual Reality - Lochhead, Ian; Hedley, Nick; Çöltekin, Arzu; Fisher, Brian (Frontiers in Virtual Reality, 2022)
Advancements in extended reality (XR) have inspired new uses and users of advanced visualization interfaces, transforming geospatial data visualization and consumption by enabling interactive 3D geospatial data experiences in 3D. Conventional metrics (e.g., mental rotations test (MRT)) are often used to assess and predict the appropriateness of these visualizations without accounting for the effect the interface has on those metrics. We developed the Immersive MRT (IMRT) to evaluate the impact that virtual reality (VR) based visualizations and 3D virtual environments have on mental rotation performance. Consistent with previous work, the results of our pilot study suggest that mental rotation tasks are performed more accurately and rapidly with stereo 3D stimuli than with 2D images of those stimuli.